Reflection of political restructuring on urban symbols: the case of presidential palace in Ankara, Turkey - Orhan, Ezgi (Journal of Architecture and Urbanism, 2016)
Ankara, capital of Turkey has been the revolution space of the country after the proclamation of republic in 1923. The city has carried out the urban symbols of the republican ideology and modernity vision created by the nationalist administrators and elites. The newly established state used architecture and urban planning in transmitting the ideals of national unity and sovereignty by breaking off its ties from Ottoman heritage. After the span of eighty years, Turkey has experienced a new political hegemony. Post-2000s’ political approach changed the urban symbols of early Republican period and redesigned the capital in line with its ideological basis. One of the most concrete transformations is observed in the presidential palace of the country which conveys the political intents of each period through its spatial and architectural organizations. This study, therefore, aims to put forward the change in urban symbols and their meanings by focusing on the presidential palace. The palaces are investigated in observational domains; their spatial configurations, buildings, and symbols in relation to the political intents on urban areas and public realm. This paper concludes that in both periods presidential palaces with respect to their spatial and architectural designs are regarded as the icons in representing the dominant political power; the former used it as an instrument of national sovereignty whereas the latter used it as a mark of dominancy over the nation.